Guidelines for Inspection of Companion and Commercial Animal Establishments - Warwick, Clifford; Jessop, Mike; Arena, Phillip; Pilny, Anthony; Steedman, Catrina (Frontiers in Veterinary Science, 2018)
Various establishments exist in which animals are held for a variety of reasons. Historically, the management and inspection of animals in commerce and in private keeping have involved a considerable degree of arbitrary evaluation based on the personal experience of the vendor, keeper, advisor or inspector. Accordingly, relevant protocols and standards are subject to considerable variation. Relatedly, diversity of traded and privately kept species generates significant challenges for those responsible for facility management and inspection alike. Animal welfare and public health and safety are constant and major concerns that require objective methodologies to monitor and control. This report focuses on establishments concerned with the boarding, breeding, storage, vending or handover of animals intended for human ‘companions’ or ‘pets’, and aims to provide universal objective information for essential husbandry, inspection protocols and an allied inspection assessment tool for scoring establishments.